What do young children know about knowing? a cognitive-developmental study of preschoolers' understanding of knowledge acquisition - Liwag, Ma. Emma Concepcion D.; Tiangco, Luz Erlinda Marie M. (Philippine Journal of Psychology, 1999)
Four experiments were conducted to investigate preschool children's understanding of knowledge acquisition, with 180 male and female children aged 3-, 4-, and 5-years old and enrolled in Quezon City preschools participating. Experiment I showed that children as young as 3 years old can ably differentiate among three knowledge sources, namely Seeing, Feeling and Telling, and this ability was shown to significantly improve with age. Experiment 2 determined whether young children understand that sensory experiences create personal knowledge. Results indicated that 3-year-olds have grave difficulties causally connecting their knowledge with its source while older children can correctly justify the source of their knowledge. Experiment 3 compared children's ability to identify the direct or non-inferential origins of their knowledge (e. g., Seeing, Feeling, or Telling) with their ability to identify an inferential source. Again, age had a significant effect with older children performing better, but overall, there were no significant differences in performance between non-inferential and inferential tasks, contrary to expectations. Finally, Experiment 4 assesses preschool children's understanding that certain types of knowledge depend on the specific mode of sensory experience involved. In this task, age once more had a significant effect, and children performed better when Feeling was the sensory modality. The results from the four experiments were related to a theory of understanding knowledge acquisition in the preschool years (Wimmer, Hogrefe, & Sodian, 1988). Practical implications for early childhood cognitive development are also dicussed.